Mechanism of ultrasound-induced microstructure modification in Al–Zr alloys. (15th October 2020) - Jung, Jae-Gil; Cho, Young-Hee; Kim, Sung-Dae; Kim, Soo-Bae; Lee, Sang-Hwa; Song, Kyung; Euh, Kwangjun; Lee, Jung-Moo
Abstract: This work probes the effect of ultrasonic melt treatment (UST) on primary intermetallic particles and α-Al using pure Al and Al–Zr alloys (Al–0.3Zr–0.1Ti, Al–0.5Zr, Al–0.5Zr–0.5Mg–0.9Si) solidified at various cooling rates of 0.2–70 K s −1 . The application of UST is shown to decrease the size and increase the number density and volume fraction of D023 -structured primary Al3 Zr and Al3 (Zr, Ti) particles with a high nucleation potency for α-Al formation. High-resolution transmission electron microscopy analysis reveals that the cavitation-induced wetting and dispersion of γ-Al2 O3 inoculant particles contribute to the refinement of primary intermetallic particles. The grain size of Al–Zr alloys increases with increasing cooling rate because of the concomitantly reduced formation of primary intermetallic inoculant particles. The UST-induced refinement of primary Al3 Zr particles and the increased number density lead to grain refinement in Ti-free Al–Zr alloys. For the Ti-containing Al–Zr alloy, UST-induced grain refinement is achieved only at a very low cooling rate of 0.2 K s −1, possibly because of the side effects of UST on the growth-restricting influence of Ti. The fast cooling–induced solidification enables significant age-hardening by L12 -Al3 Zr nanoprecipitation (~5 nm) and is not affected by UST. Thus, this study shows that UST can be used to reduce the degree of grain coarsening of age-hardenable Al–Zr alloys at high cooling rates. Graphical abstract: Image, graphical abstract